(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2020)
From the literature it is clear that the interaction between the superstructure and the soilfoundation has not been taken into consideration in most of the research work. The effect of construction phase and mode of superstructure loading on the response of structure and foundation has not been given attention. The purpose of this study is to formulate and investigate analytical model for natural period of reinforced frame buildings (low, medium and high rise) based on RPA2013 with fixed and flexible base. Three types of soil hard, medium and soft are used; isolated foundation for hard and medium soil – sites S1, S2 and raft foundations for soft soil sites S3 and S4. For analysis SAP2000 software is used and the soil flexibility is incorporated using Winkler approach (spring model) and compared with Newmark Rosenblueth, Deleuze and Gazetas methods. A comparative study has also been done on spectral acceleration coefficient (S/g) for buildings with fixed and flexible bases founded on different soils.